Penguatan Usaha Mikro, Kecil dan Menengah Melalui Edukasi Penentuan Harga Jual Dalam Menghadapi Persaingan Usaha - Ulfah, Yana; Setiawaty, Agus (ANDIL Mulawarman Journal of Community Engagement, 2024)
Micro, Small and Medium Enterprises (MSMEs) are businesses that are relatively stable and strong in today's high competition. Therefore, efforts to develop MSMEs are very important for the Indonesian economy. Unfortunately, this hope seems to encounter obstacles in the field, especially in terms of operational activities when determining the selling price of the products produced. This activity aims to support the strengthening of MSMEs by providing education about determining product selling prices to business actors. This activity was carried out using lecture methods and intense mentoring for MSME actors. This activity discovered the fact that selling prices were determined based on estimates or market prices alone without considering other important cost components in production. Through this activity, it is hoped that the obstacles faced by MSMEs in determining the right selling price can be resolved so that MSMEs can successfully face business competition and at the same time improve the community's economy.